2012
DOI: 10.1037/a0028265
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal predictors of early therapeutic alliance in a transdiagnostic cognitive-behavioral treatment for adolescents with anxiety and depression.

Abstract: The importance of therapeutic alliance in predicting treatment success is well established, but less is known about client characteristics that predict alliance. This study examined alliance predictors in adolescents with anxiety and/or depressive disorders (n=31) who received a transdiagnostic cognitive-behavioral treatment, the Unified Protocol for the Treatment of Emotional Disorders in Youth (Ehrenreich, Buzzella, Trosper, Bennett, & Barlow, 2008) in the context of a larger randomized controlled trial. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 84 publications
1
39
0
2
Order By: Relevance
“…Despite Levin et al. () study, the remaining literature examining social competence in relation to alliance has linked both positive (e.g., social support) and negative (e.g., hostility) social constructs to alliance. However, these studies included different age ranges, such as adults, and/or different presenting problems, such as oppositional behaviors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite Levin et al. () study, the remaining literature examining social competence in relation to alliance has linked both positive (e.g., social support) and negative (e.g., hostility) social constructs to alliance. However, these studies included different age ranges, such as adults, and/or different presenting problems, such as oppositional behaviors.…”
Section: Discussionmentioning
confidence: 94%
“…This notion is partly supported in the extant literature. For instance, in the one study that included anxious (and depressed) youth, relationship quality with a caregiver and perceived social support was related to stronger therapeutic alliance during a cognitive–behavioral treatment (Levin et al., ). However, adolescents’ perceptions of their own social competence in relationships were not related to alliance (Levin et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Orlinsky et al () reported over 1,000 research findings that show an association between therapeutic alliance and client outcomes. Also, research findings have demonstrated that the therapeutic alliance early in the treatment process is a stronger predictor of counseling outcomes than the alliance later in the treatment process (Hersoug, Monsen, Havik, & Høglend, ; Levin, Henderson, & Ehrenreich‐May, ). Based on numerous studies and meta‐analyses, researchers have reported that the client's view of the alliance is typically a better predictor of outcome than the counselor's view (Bachelor & Horvath, ; Castonguay, Constantino, & Holtforth, ; Horvath & Bedi, ; Horvath & Symonds, ).…”
Section: Counseling Outcomesmentioning
confidence: 99%
“…Given that alliance is considered an important component of client engagement and better treatment outcome (e.g., Gaston, 1991), the co-occurrence of MDD with PTSD may potentially hinder clients’ motivation for forming a strong relationship with their therapist and fully engaging in the treatment. Finally, recent evidence suggests that therapists report a weaker alliance with patients who present with anxiety and co-occurring depression than with individuals who present with anxiety alone (Constantino & Smith-Hansen, 2008; Levin, Henderson, Ehrenrich-May, 2012). …”
mentioning
confidence: 99%